Predicting Fame and Fortune: PageRank or Indegree? - Upstill, Trystan; Craswell, Nick; Hawking, David (Proceedings of the Australasian Document Computing Symposium, ADCS2003, 2003)
Measures based on the Link Recommendation Assumption are hypothesised to help modern Web search engines rank ‘important, high quality’ pages ahead of relevant but less valuable pages and to reject ‘spam’. We tested these hypotheses using inlink counts and PageRank scores readily obtainable from search engines Google and Fast. We found that the average Google-reported PageRank of websites operated by Fortune 500 companies was approximately one point higher than the average for a large selection of companies. The same was true for Fortune Most Admired companies. A substantially bigger difference was observed in favour of companies with famous brands. Investigating less desirable biases, we found a one point bias toward technology companies, and a two point bias in favour of IT companies listed in the Wired 40. We found negligible bias in favour of US companies. Log of indegree was highly correlated with Google-reported PageRank scores, and just as effective when predicting desirable company attributes. Further, we found that PageRank scores for sites within a known spam network were no lower than would be expected on the basis of their indegree. We encounter no compelling evidence to support the use of PageRank over indegree.
://research.microsoft.com/users/nickcr/pubs/upstill_adcs03.pdf